Why managing sciatica is difficult: patients' experiences of an NHS sciatica pathway. A qualitative, interpretative study. Issue 6 (11th June 2020) - Ryan, Clare; Pope, Catherine J; Roberts, Lisa
Abstract : Objectives: Amid a political agenda for integrated, high-value care, the UK is implementing its Low Back and Radicular Pain Pathway. To align care with need, it is imperative to understand the patients' perspective. The purpose of this study was, therefore, to explore how people experience being managed for sciatica within an National Health Service (NHS) pathway. Design: Qualitative interpretative study. Setting: Musculoskeletal Service in an NHS, Primary Care Trust, UK. Participants: The sample comprised 14 people aged ≥18 years with a clinical presentation of sciatica, who were currently under the care of a specialist physiotherapist (the specialist spinal triage practitioner), had undergone investigations (MRI) and received the results within the past 6 weeks. People were excluded if they had previously undergone spinal surgery or if the suspected cause of symptoms was cauda equina syndrome or sinister pathology. Participants were sampled purposively for variation in age and gender. Data were collected using individual semi-structured interviews (duration: 38–117 min; median: 82.6 min), which were audio-recorded and transcribed verbatim. Data were analysed thematically. Results: A series of problems with the local pathway (insufficient transparency and information; clinician-led decisions; standardised management; restricted access to specialist care; and a lack of collaboration between services) made it difficult for patients to access the management they perceived necessary. Patients were therefore required to be independent and proactive or have agency. This was, however, difficult to achieve (due to the impact of sciatica and because patients lacked the necessary skills, funds and support) and together with the pathway issues, this negated patients' capability to manage sciatica. Conclusions: This novel paper explores how patients experience the process of being managed within a sciatica pathway. While highlighting the need to align with recommended best practice, it shows the need to be more person-centred and to support and empower patient agency. Trial registration number: ClinicalTrials.gov reference (UOS-2307-CR); Pre-results.